The Impact of Product and Process Innovation on Performance of Small Enterprises - Luqman Al Hakim Mohd Noor; Ahmad, Nurazwa; Nor Kamariah Kamaruddin (Research in Management of Technology and Business, 2024)
Small enterprises are important for the development of any country as they assist economic growth and create employment opportunities for urban and rural communities. Small enterprises employing low levels of labor productivity and low technology use, shortage of skilled workers and skills mismatches, inability to retain permanent staff due to local talent migration, low financial ability and shortage of capital, management and marketing constraints, poor infrastructure and forging relationships with multinational companies. Innovation is an important factor that small enterprises need to consider in order to keep their company performing well, competitively and innovatively despite all the challenges. This study aims to examine the effect of product innovation and process innovation on small enterprise performance. A total of 53 usable questionnaire responses were returned in this study consisting of small companies represented by the owners of the company. Descriptive results showed a high value of mean scores for all variables. Furthermore, the findings of correlation analysis showed a positive significant value, r=0.508 (p<0.05) between process innovation and innovation performance, whereas the multiple linear regression model is, R2=0.264 (p<0.01). The model was proven a significant impact of process innovation on innovation performance for the small enterprises. While low- or medium-sized companies may lag behind large firms in product innovation, they often excel in process innovation. The combination of product and process innovations significantly enhances performance, with a stronger emphasis on process-oriented improvements aimed at boosting productivity and quality rather than product development.